Chemical composition and antimicrobial activity of leaves essential oil of Juniperus communis (Cupressaceae) grown in Republic of Macedonia - Floresha Sela; Marija Karapandzova; Gjose Stefkov; Ivana Cvetkovikj; Elena Trajkovska-Dokik; Ana Kaftandzieva; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2013)
Chemical composition and antimicrobial activity of essential oils isolated from leaves of three different samples of wild growing Juniperus communis L. (Cupressaceae) from R. Macedonia was investigated. Essential oil yield ranged from 7.3 to 9.0 ml/kg. Performing GC/ FID/MS analysis, ninety components were identified, representing 86.07-93.31% of the oil. The major components of the leaves essential oil (LEO) were α-pinene (21.37-28.68%) and sabinene (2.29-16.27%), followed by limonene, terpinen-4-ol, β-elemene, trans-(E)-caryophyllene, germacrene D and δ-cadinene. Antimicrobial screening of the LEO was made by disc diffusion and broth dilution method against 16 bacterial isolates of Gram positive and Gram negative bacteria and one strain of Candida albicans. Two bacteria, Staphylococcus aureus and Streptococcus pyogenes were sensitive to antimicrobial activity of LEO (MIC = 125 µl/ml). Additionally, LEO showed moderate antimicrobial activity against Streptococcus agalactiae, Haemophilus influnzae, Corynebacterium spp. and Campylobacter jejuni (MIC > 500 µl/ml). Candida albicans, Staphylococcus epidermidis, Acinetobacter spp., Salmonella enteritidis, Shigella flexneri, Klebsiella pneumonia, Pseudomonas aeruginosa and Proteus mirabilis were completely resistant to the antimicrobial effects of this.